Supply chain management in the global context - Werner Delfmann; Sascha Albers (University of Cologne, Department of Business Policy and Logistics, 2000)
The relevance of a global perspective on business operations is evident as nowadays every introduction to a major or minor text on managerial issues highlights the new challenges and risks of the globalizing world economy. It is apparent that in this paper, this opinion is shared. As globalization is evolving, all corporate activities have to cope with the influence as well as the opportunities that arise from it. Here, we will focus on the implications for business logistics and especially consider the impact on supply chain management. We will depict the basic concept of supply chain management (SCM) as well as the phenomenon of globalization for subsequently highlighting the characteristic problems that arise for SCM in the global context. In the first part, we will treat the problems and underlying ideas of the SCM concept and its relation to logistics. Afterwards, we will have a closer look on globalization and its effects on logistics and SCM. In the last part of this section we will elucidate some aspects appearing to be of central relevance in global SCM.
Keywords: 650